Endarachne binghamiae Extract Ameliorates Inflammatory Responses in Macrophages Through Regulation of MAPK, NF-kB and PI3K/AKT Pathways, and Prevents Acute Lung Injury in Mice - Sang-Hoon Lee; Sang-Seop Lee; Ga-Young Lee; Seung-Yun Han; Dong-Sub Kim; Bong-Ho Lee; Yung-Choon Yoo (Life)
In this study, the anti-inflammatory effect of the hot water extract of Endarachne binghamiae (EB-WE), a type of marine brown algae, was investigated in LPS-stimulated RAW 264.7 cells and an acute lung injury (ALI) mouse model induced by intranasal LPS administration. Treatment with EB-WE significantly inhibited NO and pro-inflammatory cytokine (TNF-a and IL-6) production in LPS-stimulated RAW 264.7 cells. In mRNA analysis, the expression of pro-inflammatory cytokines, COX-2, and iNOS mRNAs, was down-regulated by EB-WE treatment. The phosphorylation of MAPK, IkB, and PI3K/AKT molecules responsible for signal pathways during inflammation in LPS-stimulated macrophages was also significantly inhibited by EB-WE. In an in vivo model for ALI, oral administration of EB-WE significantly reduced the level of pro-inflammatory cytokines (TNF-a, IL-1b, and IL-6) and chemokines (MCP-1, CXC-16, CXCL1, and TARC) in serum or bronchoalveolar lavage fluid (BALF) of mice. Similarly to the results in LPS-stimulated RAW 264.7 cells, treatment with EB-WE significantly inhibited intracellular signal pathways mediated by MAPK, IkB, and PI3K/AKT in lung tissues of mice with ALI, and also decreased the expression of mRNAs of inflammatory mediators such as TNF-a, IL-6, iNOS, and COX-2. Furthermore, the inhibitory effect of EB-WE on ALI was apparently confirmed in histological examination through lung tissue staining. Taken together, it is clear that EB-WE has potential activity to effectively ameliorate the inflammatory responses in macrophages through down-regulation of MAPK, NF-kB, and PI3K/AKT activation, and suppress acute lung injury induced by LPS. These findings strongly suggest that EB-WE is a promising natural product beneficial for developing preventive treatments and cures of inflammation-related diseases.